Developing Fire Resistant Compound From Household Material - MOHD ASRI, LUQMAN AL HAKIM (Enhanced Knowledge in Sciences and Technology, 2024)
**Abstract:***Title: Investigating the Thermal and Fire-Resistant Properties of Composite Materials*This technical paper explores the influence of key components, including baking soda, cornstarch, and PVA glue, on the thermal conductivity and fire resistivity of composite materials. A series of experiments were conducted to analyze the variations in wet and dry weight, thermal conductivity, and fire resistivity under different concentration ratios. Results indicate that increasing baking soda content correlates with enhanced thermal conductivity and fire resistivity. Conversely, higher cornstarch concentrations lead to reduced thermal conductivity. The addition of PVA glue demonstrated a positive impact on fire resistivity. This study sheds light on the nuanced interplay of these components in composite materials, offering valuable insights for applications requiring thermal and fire-resistant characteristics.